2018
DOI: 10.1002/jcb.27289
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of exosomal microRNAs during chondrogenic differentiation of human bone mesenchymal stem cells

Abstract: The aim of the current study was to compare the expression of microRNAs (miRNAs) in exosomes derived from human bone mesenchymal stem cells (hBMSCs) with and without chondrogenic induction. Exosomes derived from hBMSCs were isolated and identified. Microarray analysis was performed to compare miRNA expression between exosomes derived from hBMSCs with and without chondrogenic induction, and quantitative real‐time polymerase chain reaction (qRT‐PCR) was used to verify the differentially expressed miRNAs. hBMSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 29 publications
0
87
0
Order By: Relevance
“…This suggests that synovial tissue may regulate chondrocytes by secreting exosomes. Number of articles [15][16][17][18][19][20][21][22] has conducted detailed studies on how to extract cell supernatants and exosomes in body fluids, but few of articles had studied the extraction and identification of exosomes in tissues. To the best of our knowledge, any article has been published on how to extract and identify exosomes from synovial tissue.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that synovial tissue may regulate chondrocytes by secreting exosomes. Number of articles [15][16][17][18][19][20][21][22] has conducted detailed studies on how to extract cell supernatants and exosomes in body fluids, but few of articles had studied the extraction and identification of exosomes in tissues. To the best of our knowledge, any article has been published on how to extract and identify exosomes from synovial tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes, as important paracrine components, are involved in maintaining normal physiological functions, mediating inter-cell communication, and inducing changes in cell functions and processes by delivering various types of bioactive microRNAs, proteins, and unique gene products 9,10,24 . These microRNAs might serve as vital inducers of HUCMSC differentiation into chondrocytes, such as the exosomal miR-92a-3p, exosomal miR-95-5p, exosomal miR-320c, and exosomal miR-135b, which can regulate cartilage development and homeostasis [25][26][27][28] . These ndings suggest that the active molecules in exosomes may be an important mechanism underlying their ability to promote chondrogenesis of HUCMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…There are two ways to load drugs into exosomes, one is to load drugs into the donor cell of exosomes, such as using transfection and co-incubation; the other is to load drugs into exosomes after they are secreted, such as direct mixing, which the loading efficacy is a big concern. At present, most researchers prefer to obtain the exosomes for OA therapy with high expression of miRNA or lncRNA from modified MSCs [22,[44][45][46] . Exosomal miR-92a-3p [22] , exosomal lncRNA-KLF3-AS1 [44] , exosomal miR-140-5p [45] and exosomal miR-320c [46] from transfected MSCs have been reported to have significant therapeutic effects on OA in vivo and in vitro.…”
Section: Exosomes From Molecular Engineered Cellsmentioning
confidence: 99%
“…At present, most researchers prefer to obtain the exosomes for OA therapy with high expression of miRNA or lncRNA from modified MSCs [22,[44][45][46] . Exosomal miR-92a-3p [22] , exosomal lncRNA-KLF3-AS1 [44] , exosomal miR-140-5p [45] and exosomal miR-320c [46] from transfected MSCs have been reported to have significant therapeutic effects on OA in vivo and in vitro. Furthermore, it was reported that primary chondrocytes also could be modified to serve as the donor cells of exosomes [24] .…”
Section: Exosomes From Molecular Engineered Cellsmentioning
confidence: 99%
See 1 more Smart Citation